Impact of Workplace Politics on Academic Staff Productivity in Nigerian Universities - Adeniyi Jamiu, Yusuf; Muinat Abiodun, Ibrahim (Management Analytics and Social Insights, 2025)
This study investigates the impact of workplace politics on academic staff productivity in Nigerian universities, offering insights into how political dynamics within the workplace influence staff performance. Using a cross-sectional survey design, data were collected from academic staff across several universities, focusing on their perceptions of workplace politics, job satisfaction, and self-reported productivity levels. The analysis reveals a significant negative correlation between workplace politics and staff productivity, highlighting that a politically charged environment—characterized by favoritism, lack of transparency, and politically motivated decisions—can demotivate employees and reduce their output. This study contributes to existing literature by providing empirical evidence on the detrimental effects of workplace politics in the academic setting, emphasizing the need for transparent management practices to foster a more productive work environment. Recommendations are made for university administrators to mitigate the impact of workplace politics and enhance employee motivation.